The Nanolithography Toolbox - Balram, Krishna C; Westly, Daron A; Davanço, Marcelo; Grutter, Karen E; Li, Qing; Michels, Thomas; Ray, Christopher H; Yu, Liya; Kasica, Richard J; Wallin, Christopher B; Gilbert, Ian J; Bryce, Brian A; et al. (Journal of research of the National Institute of Standards and Technology, 2016)
This article introduces in archival form the Nanolithography Toolbox, a platform-independent software package for scripted lithography pattern layout generation. The Center for Nanoscale Science and Technology (CNST) at the National Institute of Standards and Technology (NIST) developed the Nanolithography Toolbox to help users of the CNST NanoFab design devices with complex curves and aggressive critical dimensions. Using parameterized shapes as building blocks, the Nanolithography Toolbox allows users to rapidly design and layout nanoscale devices of arbitrary complexity through scripting and programming. The Toolbox offers many parameterized shapes, including structure libraries for micro- and nanoelectromechanical systems (MEMS and NEMS) and nanophotonic devices. Furthermore, the Toolbox allows users to precisely define the number of vertices for each shape or create vectorized shapes using Bezier curves. Parameterized control allows users to design smooth curves with complex shapes. The Toolbox is applicable to a broad range of design tasks in the fabrication of microscale and nanoscale devices.
Keywords: nanoscale curved features; CAD; nanophotonic; nanoscale design; nanofluidic; nanofabrication; nanoplasmonic; nanoscale devices; lithography